Software-in-the-Loop Simulation of a Gas-Engine for the Design and Testing of a Wind Turbine Emulator - Alexander Rohr; Clemens Jauch (Energies, 2021)
In order to investigate the grid integration of wind turbines (WT) of various scales and designs, a wind turbine emulator (WTE) is being built in Flensburg within the state-funded project GrinSH. The special feature of this WTE is the use of a large gas engine instead of an electric motor to emulate the behavior of a WT. In order to develop the controls of this innovative WTE and to design the upcoming test runs under safe conditions, a software in the loop model (SILM) was applied. This SILM contained a mathematical model of the wind turbine, mathematical models of the gas engine with an integrated controller, and a model of the generator and frequency converter unit, as well as a preventive modulator of the reference signal (PMRS). The PMRS module converts the reference signal of the emulated WT in such a way that the dynamics of the engine components can be calculated and balanced in advance to enable the required behavior of the entire SILM despite the dynamics of the gas engine. It was found that the PMRS module, developed and tested in this work, increased the ability of the WTE, based on a gas engine, to reproduce the dynamics of a WT.